ORIENTALIST TURK(EY) IMAGE CREATED THROUGH WESTERN PHILOSOPHY OF 18TH CENTURY AND ITS REFLECTIONS ON CINEMA: AN ANALYSIS ON IMDB - Akan YANIK (Fırat University, 2019)
Orientalism adventure taking place with such literary works as 1001 Arabian Nights still continues on television and cinema which are the dominant mass media of today. Especially after 1930, through the liberalization of cinema, orientalism could spread to wide areas when the films are turned into not only products but also international investments which carry out mass production. Cinema, being the most important and efficient visual art of our era, not only reflects its society or its cultural values but also acts as a mirror reflecting the position where the society, company or institution, which produces the films, puts the other societies and how they position their value judgements. Through this representation and presentation, societies, nations or value judgements can be glorified or trivialized. This study is based on the assumption that 18th century philosophers have laid the foundation of the image of Turk(ey) in the West and the current image of Turk(ey) is composed of the effects of this foundation. In this regard, in literature review of the study, it was determined how 18th century orientalist philosophers have built the image of Turk, how they have seen Turkey under the relevant era and circumstances from Western point of view and how they have created the knowledge about the image of Turk on the base of enlightenment with Western perspective. In the analysis part of the study; cinema films which are chosen among IMDB (International Movie Database) Top 1000 films and in which the discourse of “Turk” is explicitly expressed have been analyzed in order to establish a link between the history and today in the perspective of the West towards the East. In the conclusion part of the study, under the light of films which are analyzed and their indications, the image of “Turk(ey)” has been tried to be interpreted from the framework of communication and public relations.